The effect of water stress on various of growth and proline, catalase, SOD in sesbania aculeata - m Kamrani; a Sateei; a Nourinia (فیزیولوژی محیطی گیاهی, 2007)
In this study, effects of dry stress on growth parameters, proline content, glycine betaine, catalase, proxidase, and superoxide dismutase (SOD) were investigated in Sesbania aculeate L. This study was carried out fewer than 7 potting conditions on 7 treatments. Growth parameters such as number of leaves, area leaf, length of shoots, and number of shoots were measured during 4 stage of growth. Results indicated that increase in drought stress caused many effects on morphology and enzymes activities also decrease on growth, number of leaves, leaf area and increase in growth of root rather than shoot. Drought stress did not caused significant difference in the number of shoots. Increase in drought stress also lead to increase in glycine betaine (GB), and proline content in root and leaf. Increase in proline and GB content in leaf was higher than root. Drought stress also caused increase in catalase activity in root and leaves, and more stress also lead to more activity. Drought caused increase in peroxidase activity in leaves and root, but increases in this activity by increasing stress were only observed for root. Superoxide dismutase activity in leaves was not affected significantly by drought stress, but increased in root, by increase in stress.